2018
DOI: 10.1002/jhet.3253
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Synthesis of Antimicrobial Agents Containing Carbazole and Thiazole Moieties

Abstract: An efficient synthesis of new derivatives of carbazole incorporated with thiazole moiety via the reaction of carbazole thiosemicarbazone with hydrazonoyl chloride under microwave irradiation. The spectral results and the electronic absorption data proved the postulated structures of the resulting compounds. The starting thiosemicarbazone and all the new derivatives were evaluated against two fungi, four G+ bacteria and G− bacteria. The results obtained explore the high potency of some of the tested compounds c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…Among the N-substituted carbazole derivatives synthesised by Zhang et al [ 10 ], 9-(4-(-imidazol-1-yl)butyl)-9 H -carbazole showed the best antimicrobial activity, and its MIC values were 1–64 µg/mL. The substitution of carbazole with the thiazole ring and/or phenyl ring strongly increased its activity against different microorganisms [ 11 ]. Gu et al [ 12 ] indicated that some derivatives of N-substituted 1 H -dibenzo[a,c]carbazole demonstrate high antimicrobial activity, compared with the potential of antibiotics such as ketoconazole and amikacin.…”
Section: Discussionmentioning
confidence: 99%
“…Among the N-substituted carbazole derivatives synthesised by Zhang et al [ 10 ], 9-(4-(-imidazol-1-yl)butyl)-9 H -carbazole showed the best antimicrobial activity, and its MIC values were 1–64 µg/mL. The substitution of carbazole with the thiazole ring and/or phenyl ring strongly increased its activity against different microorganisms [ 11 ]. Gu et al [ 12 ] indicated that some derivatives of N-substituted 1 H -dibenzo[a,c]carbazole demonstrate high antimicrobial activity, compared with the potential of antibiotics such as ketoconazole and amikacin.…”
Section: Discussionmentioning
confidence: 99%
“…Of the compounds evaluated, adduct 33d was unquestionably the most potent antifungal carbazole derivative, with MIC values ranging from 1.2 μM ( S. cerevisiae ) to 12 μM ( A. flavus ), which was comparable to that detected by amphotericin-B at 1 μM. In 2018, Farghaly et al prepared several thiazole-containing carbazoles through microwave-assisted synthesis [ 52 ]. The synthesis started from 9-ethyl-9 H -carbazole-3-carbaldehyde and thiosemicarbazide to produce intermediate 36 , which was then reacted with different hydrazonyl chlorides to afford carbazole derivatives 37a-f and 38a-e ( Figure 6 ).…”
Section: Antibacterial and Antifungal Activities Of Carbazole Derivat...mentioning
confidence: 99%
“…Alkyl, aryl, or heterocyclic substituents can be added to any of the 2-, 4-, or 5-position of the thiazole ring by carefully selecting the reactants. 38,39 In recent years, a series of oxidative systems, such as HX/ DMSO, 40 43 and (CH 3 ) 3 SiX-KNO 3 , 33 have been disclosed. In 2022, Lu and co-workers presented 2,4-diphenyl thiazole synthesis by the reaction of sulfoxonium ylide and thiobenzamide under the catalysis of palladium (Scheme 1A, i).…”
Section: Introductionmentioning
confidence: 99%